MODERN ELITE SOCIETY AND NATIONAL MOVEMENT - Gunawan, Restu (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
Since the reformation happened to this country, publications on several main events, which were sometimes causing some resentment, have been appeared. They include a widespread corruption issue involving executive, legislative, judicative or private elements; a notorious issue of a house member caught up as he played his gadget to watch a porn video; as well as an issue of a ruined PSSI congress held on May 20, 2011.  Then, why don’t we, as a nation well known for its decency and friendliness, show our tolerance? What is wrong with us? As this question showed up to the ground, there were also excuses replying; we are not ready for democracy, our leaders are indecisive, our education system was so messy, and so on and so forth.To analyze this, we can refer to a certain past moments. Koesome Oetoyo, in ‘Pewarta Prijaji’, August 1900 explained that priyayi were those who worked as clerk, teacher, foreman, police agent, and etc. Koesome Oetoyo, in ‘Pewarta Prijaji’, August 1900 explained that priyayi were those who worked as clerk, teacher, foreman, police agent, etc. Accordingly, those involving in the aforementioned cases are priyayi, even a high class priyayi. This article focuses on study of modern elite society and national movement in Java since 1900-1942.